(untitled) (Research, Society and Development, 2021)
Objective: The aim of the present study is to report a case of severe odontogenic infection in a geriatric patient, addressing the clinical aspects and the surgical approach. Case Report: Male patient, 85 years old, with swelling in the right submandibular, right oral, submentual and severe pain related to tooth 46, which was clinically compromised by caries in the buccal region. Antibiotic therapy with clindamycin and surgical procedure were performed under general anesthesia of tooth extraction 46 and drainage of the submandibular, submentual and buccal facial spaces. In the immediate postoperative period, the patient developed a stroke and was referred to the intensive care unit (ICU), where he remained for 7 days. After that, he recovered well and was discharged on the tenth day after surgery. The patient is in a six-month postoperative follow-up, with no signs of complications or sequelae caused by the treatment performed. Conclusion: The treatment of odontogenic infections in elderly patients should be performed with great caution, especially in those with systemic involvement that can trigger trans or postoperative complications. In addition, adequate knowledge of the dentist’s anatomy, pharmacology and surgical approach is essential.